Posttraumatic Stress Disorder 23 Years After the 1988 Spitak Earthquake in Armenia. Issue 1 (7th March 2018) - Goenjian, Armen K.; Khachadourian, Vahe; Armenian, Haroutune; Demirchyan, Anahit; Steinberg, Alan M.
Abstract: This population‐based longitudinal study examined the rates and predictors of posttraumatic stress disorder (PTSD) among 725 differentially exposed survivors of the 1988 Spitak earthquake in Armenia, 23 years after the event. Participants had been previously evaluated in 1991. Evaluations included assessment of current PTSD (based on DSM‐5 criteria), and a variety of potential risk and protective factors. For the whole sample, the rate of PTSD attributed to the earthquake decreased from 48.7% in 1991 to 11.6% in 2012 ( p < .001). A "dose of exposure" pattern persisted, and 15.7% of participants who were in Spitak (high exposure) and 6.6% of participants who were in Kirovagan (low exposure) during the earthquake met the criteria for PTSD ( p = .003). Additionally, in 2012, another 9.9% of participants met PTSD criteria due to post‐earthquake traumas, which is a 5‐fold increase from pre‐ to postearthquake ( p < . 001). Factors positively associated with PTSD included earthquake‐related job loss, exposure to post‐earthquake traumas, depression at baseline, and chronic illness since the earthquake. Factors inversely associated with PTSD included housing assistance within two years after the earthquake, support of family and/or friends, and to a lesser degree, higher education and high living standard. These variables accounted for 23.1% of the variance in current PTSD severity scores. These findings indicate that PTSD rates subside significantly after a catastrophic disaster, although earthquake‐related PTSD persists among a subgroup of exposed individuals. Predictors of PTSD identified in this study provide guidance for planning acute and longer‐term postdisaster public mental health recovery programs.